STABILITAS TIANG PANCANG AKIBAT LIKUIFAKSI PADA PROYEK GEDUNG SANGGALA JAKARTA - Sinta Delia; Putera Agung Maha Agung (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2020)
Liquefaction is an incident where the soil losses its shear strength due to increased porewater stress due to the incident of very fast cyclic loading in a short time. Liquefaction event due to earthquakes can cause structural failure of the building. In this case, the Sanggala Building Project in Jakarta exists at location of liquefaction potential susceptible area, and design analysis only uses the data of Cone Penetration Test (CPT). Stability analysis of pile due to liquefaction potential is aimed to determine the value of the factor of safety (FS) in the area, which is analyzed by comparing the value of Cyclic Stress Ratio (CSR) due to the earthquake and Cyclic Resistance Ratio (CRR) as the soil resistance to resist liquefaction potential. Based on the analysis and calculations performed, was obtained the value of FS > 1, which means actually the soil does not have the liquefaction potential. However, this study still takes into consideration the liquefaction potential as one of requirements of local regulation when the analysis of bearing capacity of pile foundation analyzed by the method of Schmertmann (1978) in a depth of 25 m and the results was indicated by 1660,27 kN for single pile and 12081,63 kN for the group piles. Furthermore, all these results from several stability calculations, the pile foundation system stable from liquefaction potential.